The study of simultaneous desulfurization and denitrification process based on the key parameters. (July 2018) - Zeng, Yong; Zhou, Jun; Yan, Zhiying; Zhang, Xueying; Tu, Weiguo; Li, Na; Tang, Min; Yuan, Yuexiang; Li, Xiang; Cao, Qin; Huang, Yanmeng
Graphical abstract: Highlights: The biotrickling filter packed with polyurethane foam had exhibited the maximum desulfurization-denitrification effect. The S/N molar ratio decided the component of the product. The Thiobacillus, Rhodanobacter and Arenimonas genera hold absolute dominance. The S/N molar ratios and the concentration of HS − /S 2− should be controlled in 5/3 to 5/2 and <16.8 mM in actual projects. Abstract: The impacts of different S/N molar ratios and fillers (polyurethane foam, multi-surface hollow spheres, and pall rings) on the process of simultaneous desulfurization and denitrification (SDD) were studied by using anaerobic biotrickling filer (BTF). Furthermore, the SDD mechanism was described by dividing the SDD process into three stages based on pH changes: (I) increase (II) decrease and (III) stable state. The maximum desulfurization and denitrification efficiency (13.5 g-S m −3 h −1 and 3.7 g-N m −3 h −1, respectively) was achieved by applying polyurethane foam as filler. When S 2− and S 0 coexist as electron donors in the SDD system, the functional microbes degrade S 2− preferentially. The S/N molar ratios of the influent were higher, and the relative content of sulfate in the products was less. Considering the efficiency and economic benefits, polyurethane foam is suggested as fillers for practical implementations of SDD systems. The S/N molar ratios should be controlled in a 5/3 to 5/2 range and HS − /S 2− concentration should be <16.8 mM. The Thiobacillus genus with more than 40% of relative abundance is absolutely dominant in all reactors, followed by the Rhodanobacter, Arenimonas, and Truepera genera. The microbial community with the function of desulfurization–denitrification in the system had a certain degree of redundancy.